Local governments competing for the environment and green innovation-evidence from China - Kai Wan (Journal of Applied Economics)
Enhancing green innovation is the key to realizing high-quality development and the “dual-carbon” goal. This paper takes the data from Chinese cities from 2000 to 2018 as a sample to test the impact and mechanism of local governments’ competition for the environment on urban green innovation. The study found that local government competition for the environment can effectively promote urban green innovation, and the spatial spillover effect is significant and can lead neighboring cities to improve the level of green innovation jointly. The results of the mechanism test indicate that local government competition promotes green innovation through two channels: influencing fiscal expenditure bias and the establishment of development zones. Further analysis shows that the impact of government competition on green innovation has apparent spatial heterogeneity, while the double-threshold effect results in an “N”-shaped relationship between local government competition and urban green innovation.